Population size as a factor for formation of land value in settlements - Kovalchuk, I.; Patychenko, О. (Land Management, Cadastre and Land Monitoring, 2018)
Paper reflects on the features of the formation of normative monetary evaluation of land in settlements (hereinafter abbreviated as NME). The nature of the formation of the constituent of the regional differential land rent coefficient Km1 – the coefficient characterizing population size (Km1p). Ukraine settlements classifications scheme suggested, which gives a comprehensive imagination of urban and rural settlements hierarchy in the general resettlement system of the state. Influence of indicators of a population size of different categories on a residence place - the available and permanent population on NME value is analyzed. The desirability of making changes to the Order of normative monetary evaluation of land in settlements has been justified. Specifically, it is proposed to point out that the calculation of NME is based on the account of the constant population size at the beginning of the year for which normative monetary evaluation of land is being performed.Keywords: land management, urban development, normative monetary evaluation of land in settlements (NME), population.